Парадигмы жизни и творчества Тараса Шевченко и Михаила Лермонтова: попытка конфронтативного психобиографического анализа (в 205-ую годовщину со дня рождения поэтов) - Betko, Iryna (Acta Neophilologica, 2019)
Comparative studies devoted to the work of Taras Shevchenko and Mikhail Lermontov began in the 1920s. However, there are still many unresolved problems in this area. An attempt at a comparative psychological-biographical analysis makes it possible to identify the exclusive spiritual kinship of the two poets.